2015
DOI: 10.1515/sjph-2015-0024
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Sedentary Behavior and Substance use Among Adolescents in Slovenian Urban Area / Telesna Aktivnost, Oblike Sedečega Vedenja In Uživanje Psihoaktivnih Snovi Med Mladostniki V Slovenskem Urbanem Okolju

Abstract: BackgroundStudies of the relationship between leisure time physical activity, sedentary behaviour and substance use among adolescents report contradictory results. The aim of our study was to examine the association between self-reported leisure time physical activity, sedentary behaviour and alcohol, tobacco and cannabis use among adolescents in Slovenia.MethodsSubjects consisted of 822 school children aged from 14 to 16 years, living in urban area of Ljubljana and Maribor. The data was collected using the EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
3
12
0
3
Order By: Relevance
“…Similar associations are also revealed in recent cross-sectional and longitudinal studies, but with effects that differ between males and females and populations/cultures (4,6–7; Table 1). For example, in Polish high-school students, regular physical activity was negatively associated with cigarette and marijuana use in males, but not females (7); whereas, in Slovak and Czech high-school students, physical activity was negatively associated with cigarette and marijuana use in females, but not males (4,6).…”
Section: Overview Of Recent Findings In Human Males and Femalessupporting
confidence: 85%
See 2 more Smart Citations
“…Similar associations are also revealed in recent cross-sectional and longitudinal studies, but with effects that differ between males and females and populations/cultures (4,6–7; Table 1). For example, in Polish high-school students, regular physical activity was negatively associated with cigarette and marijuana use in males, but not females (7); whereas, in Slovak and Czech high-school students, physical activity was negatively associated with cigarette and marijuana use in females, but not males (4,6).…”
Section: Overview Of Recent Findings In Human Males and Femalessupporting
confidence: 85%
“…For example, in Polish high-school students, regular physical activity was negatively associated with cigarette and marijuana use in males, but not females (7); whereas, in Slovak and Czech high-school students, physical activity was negatively associated with cigarette and marijuana use in females, but not males (4,6). While socio-cultural factors likely contribute these differential effects (20), levels of exercise/physical activity also differ between males and females and populations (4,6–7); thus, exercise may interact with socio-cultural factors to differentially influence the use to drugs in males versus females within different populations.…”
Section: Overview Of Recent Findings In Human Males and Femalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, African American and Puerto Rican young adults who used cannabis were found to have a reduced probability of being obese (23), but cannabis use was also associated with low levels of sport and exercise in young Swiss men (24) and excessive television watching (a metric of SB) in Dutch adolescents (25). A study of Slovenian adolescents found no relationship between frequency of cannabis use and either SB or PA (26).…”
Section: Introductionmentioning
confidence: 99%
“…Less evidence was found for an association between sedentary behavior and substance use among adolescents [14,15,16]. Among school-going adolescents in Slovenia, computer use time (≥2 h/day) was associated with tobacco and alcohol use [14], among Hispanic adolescents, sedentary behavior was associated with alcohol use [15], and in a study among in-school adolescents in eight African countries, leisure-time sedentary behavior (3–4 h or more/day) was associated with tobacco, alcohol and drug use [16]. We are not aware of studies investigating the relationship between sedentary behavior and psychological distress and substance use among adolescents in Asia.…”
Section: Introductionmentioning
confidence: 99%